Aggression and bullying in multicultural Canada: the experiences of minority immigrant girls and young women - Khayambashi, Shila (Lexington Books, 2024)
"In Canada, first- and second-generation young immigrant women face racism, xenophobia, democratic racism, and other forms of aggression in their daily lives. This book observes and analyzes the experiences of these women from their point of view"--